An investigation into the implementation of the senior secondary agriculture curriculum in the Caprivi region of Namibia - Kasenga, Alfred (Rhodes University, Faculty of Education, Department of Education, 2007)
Shortly after independence, Namibia embarked on a major process of educational reform. It was in this reform that the apartheid educational legacy was redressed. Namibians viewed the apartheid educational system as being irrelevant and that it did not meet their needs and expectations. One of the reform aims was to involve education in the development of knowledge and skills for self sufficiency and sustainable development, therefore Agriculture was incorporated into the school curriculum as a key area to achieve this aim. Learners taking the subject are expected to be equipped with relevant theoretical and practical skills that provide a sound foundation in this discipline. This case study was undertaken to gain a better understanding about how the participating teachers perceived and implemented the Agriculture curriculum at the senior secondary school level in their schools. In carrying out the case study a qualitative research method was employed using semi-structured interviews, observation and document analysis for data collection. It would appear from this study that Agriculture is unable to fully achieve the reform ideals at the senior secondary school level, as sixteen years after independence these teachers are still teaching the subject to learners with very limited resources and academic support. This scenario shows that there are marked inconsistencies between policy and praxis, between the stated goals and aims of the reform and the curriculum designed to achieve these. In this half-thesis I therefore argue that without well qualified teachers, suitable resources and infrastructure to implement the curriculum in these schools, the pre-vocational nature of the subject as suggested in the subject policy document will be compromised. The study concludes by proposing certain teaching strategies and possibilities for systemic development that can be used to effect quality curriculum implementation in the region where the research was situated.
Keywords: Education -- Namibia; Educational change -- Namibia; Education, Secondary -- Namibia; Curriculum planning -- Namibia; Agriculture -- Study and teaching (Secondary) -- Namibia